Integrating decision aid science into game-based interactive textbooks: Improving Students’ engagement and conceptual understanding in Indonesian language classes - Achmad Fawaid; M. Noer Fadli Hidayat; Afifudin Afifudin; Ririn Anggara Setiawati; Laila Homisatun Awaliyah; Huzaimah Sindu Malika (Universitas Muhammadiyah Malang, 2026)
The complex cultural and linguistic competencies essential for Indonesian language education highlight the need for instructional models that enhance student engagement and conceptual understanding. Conventional textbook-based instruction often fails to address these needs, particularly for at-risk learners who struggle with abstract reasoning and cultural interpretation. This study examines the effectiveness of integrating decision-aid science into game-based interactive textbooks to improve student engagement and conceptual mastery. Employing a quasi-experimental mixed-methods design, this research involved 70 high school students divided into experimental and control groups. The experimental group used an interactive digital textbook embedded with decision-oriented simulations and real-time feedback, while the control group received traditional instruction. Quantitative results show that students in the experimental group demonstrated significantly greater gains in conceptual understanding, especially among moderate- and high-risk learners (p < .001), whereas the control group exhibited negligible improvement. Qualitative findings further indicate that decision-based simulations fostered meaningful engagement, enhanced the clarity of abstract concepts, and reduced performance pressure. The novelty of this study lies in demonstrating how decision-aid science—typically applied in cognitive and behavioral research—can be operationalized within digital language learning environments to scaffold reasoning, strengthen motivation, and create low-stress learning conditions.